EVALUASI SISTEM ZONASI PENERIMAAN PESERTA DIDIK BARU (PPDB) TINGKAT SMP DI KOTA SURABAYA - Hiskia Renaldi Setiawan; Tjitjik Rahaju (Universitas Negeri Surabaya, 2021)
Zoning is a procedure for admitting new students based on the area where the student lives. The process of admitting new students initially using the entrance test system. So that zoning is one example that provides opportunities for all Indonesian children without differentiating their academic abilities. This study aims to describe the evaluation of the zoning system policy for admission of new students (PPDB) at the junior high school level in the city of Surabaya. The evaluation model used has 6 indicators, namely: effectiveness, adequacy, equity, responsiveness, accuracy, and efficiency. The method used is descriptive qualitative with a literature approach (literature review) to study literature with primary sources from previous journals. The focus of the research is effectiveness, adequacy, equity, responsiveness, accuracy, and efficiency in evaluating the PPDB zoning system at the junior high school level in the city of Surabaya. The results of the study, in general, the effectiveness aspect has succeeded in implementing PPDB with quite good results, in terms of the number of enthusiasts even though the community partner pathway has obstacles and the inclusive pathway has not been successful because there are schools that do not have adequate facilities. Adequacy criteria, it is considered sufficient to solve the PPDB problem that has existed so far, namely related to favorite schools and equity. The aspect of responsiveness is not according to the needs of students, that is, many give a negative response than a positive response. The aspect of accuracy with the new rules is very beneficial for schools both suburban and city schools to have an equal position. The East Java Provincial Education Office, Surabaya City Branch, needs to review the division of the PPDB area zone and hold direct socialization to the student's guardian. Keywords: Evaluation, Policy, Zoning System, New Student Admission (PPDB) Zonasi merupakan prosedur penerimaan peserta didik baru berdasarkan wilayah tempat tinggal peserta didik yang bersangkutan. Proses penerimaan peserta didik baru yang awalnya menggunakan sistem tes masuk. Sehingga zonasi menjadi salah satu contoh yang memberikan kesempatan pada semua anak Indonesia dengan tidak membedakan kemampuan akademik. Penelitian ini bertujuan mendeskripsikan evaluasi kebijakan sistem zonasi penerimaan peserta didik baru (PPDB) tingkat SMP di kota Surabaya. Model evaluasi yang dipakai memiliki 6 indikator yaitu: efektivitas, kecukupan, pemerataan, responsivitas, ketepatan dan efisiensi. Metode yang dipakai berupa deskriptif kualitatif dengan pendekatan kepustakaan (literatur review) mengkaji literatur dengan sumber primernya dari jurnal-jurnal terdahulu. Fokus penelitian yaitu efektivitas, kecukupan, pemerataan, responsivitas, ketepatan dan efisiensi terhadap evaluasi sistem zonasi PPDB di tingkat SMP di kota Surabaya. Hasil penelitian, aspek efektifitas secara umum sudah berhasil menerapkan PPDB dengan hasil cukup baik, ditinjau berdasarkan jumlah peminat meskipun jalur mitra, warga terdapat kendala dan jalur inklusif tidak berhasil dilaksanakan karena terdapat sekolah yang belum mempunyai fasilitas yang memadai. Kriteria kecukupan, dirasa sudah cukup menyelesaikan permasalah PPDB yang selama ini ada yaitu terkait sekolah favorit dan pemerataan. Aspek responsivitas tidak sesuai kebutuhan peserta didik yaitu banyak yang memberikan respon negatif dari pada respon positif. Aspek ketepatan dengan aturan baru, sangat bermanfaat bagi sekolah baik sekolah pinggiran dan kota memiliki kedudukan sama rata. Dinas Pendidikan Provinsi Jawa Timur Cabang Kota Surabaya perlu meninjau ulang terkait pembagian zona wilayah PPDB dan mengadakan sosialisasi langsung kepada Wali murid. Kata Kunci: Evaluasi, Kebijakan, Sistem Zonasi, Penerimaan Peserta Didik Baru (PPDB)